Chemical, Physical, and Sensory Characteristics of Powdered Goat Milk with The Addition of Fruit by Evaporation Method - Nirmagustina, Dwi Eva; Khoirunnisa, Aziza; Latifah, Izza Fitri; Astuti, Widia (JURNAL ILMIAH PETERNAKAN TERPADU, 2024)
The objective of this research was to determine the physical, chemical, and sensory characteristics of powdered goat milk with the evaporation method. The study was conducted in a Complete Randomized Block Design with 3 replications. The data were processed by analysis of variance and if there was an effect of treatment, Duncan's further test was carried out. The results showed that powdered goat's milk made traditionally using the evaporation method using a pan with the addition of paste/fruit juice (dragon fruit, strawberries and oranges) had an effect on the chemical and sensory characteristics of powdered goat's milk. The protein content, crude fiber and degree of acidity of powdered goat's milk (control) were lower than powdered goat's milk with the addition of paste/fruit juice, but the fat content of powdered goat's milk (control) was higher than powdered goat's milk with the addition of paste/fruit juice. The protein, fat, crude fiber and acidity levels of powdered goat's milk with the addition of fruit juice paste were respectively 13.24 – 14.52%, 21.80 – 23.97%, 1.33 – 1.92%, 0 .83 – 1.42%. The viscosity of powdered goat's milk with the addition of paste/fruit juice (2-03 – 2.41cp) was greater than the control (1.58cp). The panelists' perception of powdered goat's milk with the addition of dragon fruit paste and orange juice was better than strawberry paste.